A new species of Loncophorus from México (Coleoptera: Curculionidae, Anthonomini) associated with Mortoniodendron (Malvales: Tiliaceae) - CLARK WAYNE, E. (Anales del Instituto de Biología serie Zoología, 2009)
ADULTS OF LONCOPHORUS ANGUSTICOLLIS, A NEW SPECIES FROM MEXICO ASSOCIATED WITH MORTONIODENDRON GUATEMALENSE STANDLEY STEYERMARK (MALVALES: TILICIACEAE), ARE DESCRIBED AND ILLUSTRATED. THE NEW SPECIES APPEARS TO BE MOST CLOSELY RELATED TO THE BRAZILIAN L. COSTALIMAI CLARK.